The crystallinity degree influence on the weather resistance of CF/PPS composites - Batista, N. L. [UNESP]; Rezende, M. C.; Botelho, E. C. [UNESP] (My University, 2016)
Polyphenylene sulphide (PPS) is a semi-crystalline high-performance thermoplastic used in the aeronautic field as a composite usually reinforced with carbon fibers. The crystallinity of semi-crystalline thermoplastics can alter significantly their mechanical properties and weather resistance. In this work, carbon fiber/polyphenylene sulphide (CF/PPS) composites were processed by hot compression molding with three different crystallinity degrees. Hygrothermal, salt spray and ultraviolet radiation climatic chambers were used to evaluate the influence of the crystallinity degree on CF/PPS composites weather resistance. The thermal and mechanical properties of the processed laminates, as obtained and weathered, were investigated by differential scanning calorimetry (DSC), interlaminar shear strength (ILSS) and acoustic vibration damping tests. The results showed that the less crystalline CF/PPS samples had their crystallinity degree increased after weathering. Salts spray exposure affected the reinforcement/matrix interphase and reduced the Young's modulus. In addition, the ultraviolet radiation reduced the Young's modulus and the interlaminar shear strength due to photooxidation. The samples with higher crystalline content were more were more severely photodegradated. In conclusion, the composites with higher crystalline degree showed to be more resistant to humidity and salinity. However, those with lower crystalline degree were more resistant to the effects of the ultraviolet radiation.
Keywords: CF/PPS; Crystallinity degree; Thermoplastic; Weather resistance